216 CYCLIC LOADING AND ULTIMATE STRENGTH OF ROTATOR CUFF REPAIRS: A COMPARISON OF AN ARTHROSCOPIC SUTURE ANCHOR TECHNIQUE AND A NOVEL ARTHROSCOPIC TRANSOSSEOUS TUNNEL TECHNIQUE IN A CADAVERIC MODEL. (1st January 2006) - Wahl, C. J.; Kweon, C.; Huber, P.
Abstract : Background: Advances in arthroscopic surgical techniques have led to continued efforts to replace many traditional "open-repair" techniques with less invasive methods utilizing arthroscopic instrumentation. Here we hope to validate, in vitro, a novel arthroscopic repair technique for rotator cuff tears of the shoulder using a method of fixation traditionally done via a large open incision of the shoulder. Study Design andMethods: This project involved two portions. The first was to repair the shoulders using each of the two methods of repair and examine the neurovasculature at risk during the transosseous tunnel procedure. The second was to utilize a materials test system (MTS) to load in a cyclic fashion each repair construct and record (a) displacement at the repair site, (b) number of cycles to failure, (c) load at ultimate failure, and (d) mode of failure. Results: Preliminary data suggest that at similar loads, there is increased displacement at the repair site in the shoulders repaired with suture anchors than those repaired using transosseous tunnels. Repair done with transosseous tunnels showed 3 mm of displacement at ≈200 N whereas repair with suture anchors showed 3 mm of displacement at ≈150 N. Data collection is ongoing currently. Conclusions: Our preliminary data suggest that the transosseous technique may provide greater holding strength compared to repairs done using suture anchors. Hopefully, we will be able to show that this novel repair technique can be performed arthroscopically in a safe and efficacious manner.